One year clinical follow up of paclitaxel eluting stents for acute myocardial infarction compared with sirolimus eluting stents - Hofma, S H (Copyright 2005 by Heart, 2005)
Objective: To compare clinical outcome of paclitaxel eluting stents (PES) versus sirolimus eluting stents (SES) for the treatment of acute ST elevation myocardial infarction. Design and patients: The first 136 consecutive patients treated exclusively with PES in the setting of primary percutaneous coronary intervention for acute myocardial infarction in this single centre registry were prospectively clinically assessed at 30 days and one year. They were compared with 186 consecutive patients treated exclusively with SES in the preceding period. Setting: Academic tertiary referral centre. Results: At 30 days, the rate of all cause mortality and reinfarction was similar between groups (6.5% v 6.6% for SES and PES, respectively, p  =  1.0). A significant difference in target vessel revascularisation (TVR) was seen in favour of SES (1.1% v 5.1% for PES, p  =  0.04). This was driven by stent thrombosis (n  =  4), especially in the bifurcation stenting (n  =  2). At one year, no significant differences were seen between groups, with no late thrombosis and 1.5% in-stent restenosis (needing TVR) in PES versus no reinterventions in SES (p  =  0.2). One year survival free of major adverse cardiac events (MACE) was 90.2% for SES and 85% for PES (p  =  0.16). Conclusions: No significant differences were seen in MACE-free survival at one year between SES and PES for the treatment of acute myocardial infarction with very low rates of reintervention for restenosis. Bifurcation stenting in acute myocardial infarction should, if possible, be avoided because of the increased risk of stent thrombosis.